Economic Integration, EU-US Trade Conflicts and WTO Dispute Settlement - Fritz Breuss (FIW - Research Centre International Economics, 2007)
Since its inception in 1995, more than 330 disputes have been raised under the WTO Dispute Settlement System. The major players in world trade - the EU and the USA - are also the busiest users of this instrument. After looking at links between economic integration and WTO involvement and a survey of the actual transatlantic WTO trade disputes, the welfare implications of the four most prominent trade disputes between the EU and the USA ("mini trade wars") are analyzed with GTAP5: the Hormones, the Bananas, the FSC and the Steel cases. The economic analysis reveals that the level of suspension of concessions hardly coincides with the level of nullification or impairment (expressed in lost trade effects) if one considers the overall welfare implications of retaliation with tariffs. The idea of "rebalancing" retaliation is a myth. Tariffs are a very bad instrument of retaliation. Maybe a mechanism of direct transfers or financial compensation would be better.
Keywords: 330; law; European law; GATT; international agreements; economic integration; globalization; international trade; model simulations; trade policy; international relations; WTO; economics; law